A promiscuous kinase inhibitor delineates the conspicuous structural features of protein kinase CK2a1. Issue 7 (8th July 2019) - Tsuyuguchi, Masato; Nakaniwa, Tetsuko; Sawa, Masaaki; Nakanishi, Isao; Kinoshita, Takayoshi
Abstract : The crystal structure of protein kinase CK2a1 in complex with 5‐iodotubercidin, an ATP‐analogue inhibitor, was determined at 1.78 Å resolution. This structure should facilitate the discovery of selective CK2a1 inhibitors. Abstract : Protein kinase CK2a1 is a serine/threonine kinase that plays a crucial role in the growth, proliferation and survival of cells and is a well known target for tumour and glomerulonephritis therapies. Here, the crystal structure of the kinase domain of CK2a1 complexed with 5‐iodotubercidin (5IOD), an ATP‐mimetic inhibitor, was determined at 1.78 Å resolution. The structure shows distinct structural features and, in combination with a comparison of the crystal structures of five off‐target kinases complexed with 5IOD, provides valuable information for the development of highly selective inhibitors.